Please solve this question
![\sqrt{} \frac{1 - \cos \: q \: }{1 - \cos \: q \: } \: = \cosec \: q \: - \cot \: q \:11−cosq1−cosq=cosecq−cotq \sqrt{} \frac{1 - \cos \: q \: }{1 - \cos \: q \: } \: = \cosec \: q \: - \cot \: q \:11−cosq1−cosq=cosecq−cotq](https://tex.z-dn.net/?f=%5Csqrt%7B%7D++%5Cfrac%7B1+-+%5Ccos+%5C%3A+q+%5C%3A+%7D%7B1+-+%5Ccos+%5C%3A+q+%5C%3A+%7D+%5C%3A+%3D+%5Ccosec+%5C%3A+q+%5C%3A+-+%5Ccot+%5C%3A+q+%5C%3A%E2%80%8B11%E2%88%92cosq1%E2%88%92cosq%E2%80%8B%3Dcosecq%E2%88%92cotq+)
Answers
Answered by
1
Answer:
Answer is : 874#57&9₹/
Step-by-step explanation:
please subscribe my channel
please mark me brain list
Answered by
3
Answer:
sec4q−sec2q=tan4q+tan2q
Step-by-step explanation:
hope its helpful dont report
Similar questions